Art and sex in Greenwich Village gay literary life after Stonewall - Picano, Felice 1944- (Carroll & Graf Publishers Distributed by Publishers Group West, 2007)
Almost a decade after the Stonewall rebellion lit the political fuse of gay liberation in 1969, its impact on the arts remained minimal. While a handful of gay plays and films and a small number of gay-themed novels were available, few of these reflected the new post-Stonewall out-of-the-closet realities. Then in 1977, three small, all-gay presses formed, which all came together in 1981 to form Gay Presses of New York--not only was it the most successful gay press of its day, but the founders had made their move at the right time and place. GPNy played a vital role in the growth of what is now gay culture, consisting of bookstores, magazines, newspapers, theater companies, and art galleries in New York, Los Angeles, and San Francisco. Here is an insider's account of the rise of contemporary gay culture.--From publisher description.